2003
DOI: 10.1152/ajpheart.00748.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of PKC in autocrine regulation of rat ventricular K+currents by angiotensin and endothelin

Abstract: Shimoni, Yakhin, and Xiu-Fang Liu. Role of PKC in autocrine regulation of rat ventricular K ϩ currents by angiotensin and endothelin. Am J Physiol Heart Circ Physiol 284: H1168-H1181, 2003 10.1152 10. /ajpheart.00748.2002 and sustained K ϩ currents were measured in isolated rat ventricular myocytes obtained from control, steptozotocin-induced (Type 1) diabetic, and hypothyroid rats. Both currents, attenuated by the endocrine abnormalities, were significantly augmented by in vitro incubation (Ͼ6 h) with the ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 52 publications
(90 reference statements)
3
46
0
Order By: Relevance
“…The down-regulation of I to might be, at least in part, responsible for the arrhythmogenic potential of angiotensin II. Experiments with isolated cardiomyocytes demonstrated that angiotensin II inhibits I to in rat and canine myocytes (15,16). As with other G q -coupled receptors (e.g.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The down-regulation of I to might be, at least in part, responsible for the arrhythmogenic potential of angiotensin II. Experiments with isolated cardiomyocytes demonstrated that angiotensin II inhibits I to in rat and canine myocytes (15,16). As with other G q -coupled receptors (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…In this animal model I to is inhibited and can be recovered by treatment with the AT1 receptor specific antagonist losartan (14). Experiments with isolated cardiomyocytes show that stimulation of the AT1 receptor results in the inhibition of I to in myocytes from rat or canine ventricle (15,16). In large mammals such as dogs or humans with substantial ventricular wall thickness, I to exhibits a transmural gradient that is vital for normal electrical activity (17,18).…”
mentioning
confidence: 99%
“…Interestingly, these modulators regulate both Kv4 channel current densities and mRNA levels. For example, angiotensin II has been implicated in the modulation of I to (35). An autocrine/paracrine release of ET-1 modulates Kv4.2 and Kv1.2 (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, angiotensin II has been implicated in the modulation of I to (35). An autocrine/paracrine release of ET-1 modulates Kv4.2 and Kv1.2 (35). Thyroid status also regulated I to density and Kv4.2 mRNA levels (36).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that Ang II may exert a direct modulation on cardiac ionic channels. Experiments have shown that stimulation of AT 1 receptor result in the inhibition of transient outward potassium channel in myocytes from rat or canine ventricle (Shimoni and Liu, 2003;Yu et al, 2000). Ang II also increases cardiac L-type Ca 2+ current (ICaL) in isolated cat myocytes (Aiello and Cingolani, 2001).…”
Section: Renin-angiotensin-aldosterone System (Raas)mentioning
confidence: 99%